Pemberdayaan Masyarakat melalui Sulaman Kapalo Samek di Nagari Kamang Mudiak, Kabupaten Agam - Jannah, Miftahul; Muchtar, Henni; Montessori, Maria; Rafni, Al (Journal of Civic Education, 2023)
This study aims to describe the implementation of community empowerment through the kapalo samek embroidery training by the familly empowerment and welfare organization. This study held at Kanagarian Kamang Mudiak, Kamang Magek District, Agam Regency. The study used in descriptive qualitative methods. The determination of informants in this study used a purposive sampling technique using data collection techniques including observation, interviews and documentation studies. The results of the study showed that the implementation of community empowerment through the training of the Kapalo Samek embroidery in terms of the aspects of planning, implementation and evaluation had not had a significant impact on improving the family economy in Kanagarian Kamang Mudiak. This can be seen from the small number of trainees who complete their training and open business after the training is given. This was due to various obstacles that arose during its implementation including: limited training participants, lack of competent human resources in the embroidery field, no follow-up of the training activities, and limited funds. The positive implications felt by the training participants, especially training participants who have opened embroidery businesses, are increasing community knowledge and skills, opening up employment opportunities and running the Kamang Mudiak nagari government program.